Diagnozowanie ubóstwa ekonomicznego na przykładzie Regionu Pomorskiego - Plecka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2008)
The main goal of this paper is a collation of methods for diagnosing subjective poverty.The comparison concerns the methods of identification of poverty in the sub-regions of the Pomeranianregion. The methods of identification proposed by the author indicate that the proposed methodsidentify poverty much more precisely than the universal methods. It can be considered to carry onthe policy of limiting poverty areas based on the local monitoring. The assembled conclusions can allowimprovement of accuracy of directing social help and at the same time can increase acceptance ofthe rules used in administering this help.